G22(P) Use of blood gas and blood ketones in management of children with gastroenteritis. (7th April 2014) - Palman, J; Misquith, R; Nathwani, N; Kinns, H; Housley, D
Abstract : Aim: To evaluate the blood gas and blood ketone abnormalities in children requiring intravenous fluids for management of gastroenteritis. Background: Gastroenteritis commonly presents to acute paediatric services. Most children are successfully managed with oral rehydration therapy (ORT). However, some children will need intravenous (IV) fluids either due to failure of ORT or persistent vomiting. Ketones are produced by metabolising fat as an alternate energy source in place of carbohydrates. It is known that raised ketone levels in conditions like diabetic ketoacidosis can contribute to nausea and vomiting. Method: There are two parts to this study. The first part is a retrospective observational study of children with gastroenteritis comparing 69 children requiring IV fluids to 87 children treated with ORT. The second part is a prospective study involving 32 children with gastroenteritis who required IV fluids. Blood sample was taken for blood gas and beta hydroxybutyrate (BOHB) levels while obtaining venous access. Treatment was carried out according to clinical requirements as per guidelines irrespective of the blood BOHB level. Results: Both data sets had similar demographics of gender, age and weight centile. The retrospective data showed those on IV fluids compared to ORT were more acidotic (p < 0.001) with a raised anion gap (p = 0.0014). The observational data demonstrated that BOHB levels prior to IV fluid therapy were normal (<0.6) in 5 patients, mildly raised (0.6–1.5) in 5, moderately raised (1.6–3) in 7 and high (>3) in 15. Following a period of IV fluids there was a reduction in acidosis (p = 0.0034) and BOHB levels (p = 0.0026). Conclusion: The majority of children with gastroenteritis who require IV fluids have a metabolic acidosis, raised anion gap and significantly raised BOHB levels. The study also illustrated a significant reduction in acidosis and BOHB with fluid management. Taking a blood gas and ketone level in children with vomiting as predominant symptom may aid in making an early decision about the need for IV fluid therapy. Using IV fluids may also ease nausea and vomiting by reducing the ketosis and acidosis in dehydrated children.